2002
DOI: 10.1093/glycob/cwf073
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an endo- -N-acetylglucosaminidase gene in Caenorhabditis elegans and its expression in Escherichia coli

Abstract: We report the identification, molecular cloning, and characterization of an endo-beta-N-acetylglucosaminidase from the nematode Caenorhabditis elegans. A search of the C. elegans genome database revealed the existence of a gene exhibiting 34% identity to Mucor hiemalis (a fungus) endo-beta-N-acetylglucosaminidase (Endo-M). Actually, the C. elegans extract contained endo-beta-N-acetylglucosaminidase activity. The putative cDNA for the C. elegans endo-beta-N-acetylglucosaminidase (Endo-CE) was amplified by polym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(42 citation statements)
references
References 24 publications
2
40
0
Order By: Relevance
“…For Endo-A and Endo-M, Man9GlcNAc2Asn was used as the substrate and the hydrolytic activity of the enzymes in the presence or absence of the respective inhibitors were measured by quantifying the hydrolytic product Man9GlcNAc using the HPAEC-PED method. 25 It was found that all the three oligosaccharide thiazolines (2)(3)(4) showed inhibitory activities against Endo-A. But the larger oligosaccharide derivative 4 was much more potent in inhibiting Endo-A activity than the tetrasaccharide and disaccharide derivatives 2 and 3, respectively ( Figure 2A).…”
Section: Inhibitory Activitiesmentioning
confidence: 98%
“…For Endo-A and Endo-M, Man9GlcNAc2Asn was used as the substrate and the hydrolytic activity of the enzymes in the presence or absence of the respective inhibitors were measured by quantifying the hydrolytic product Man9GlcNAc using the HPAEC-PED method. 25 It was found that all the three oligosaccharide thiazolines (2)(3)(4) showed inhibitory activities against Endo-A. But the larger oligosaccharide derivative 4 was much more potent in inhibiting Endo-A activity than the tetrasaccharide and disaccharide derivatives 2 and 3, respectively ( Figure 2A).…”
Section: Inhibitory Activitiesmentioning
confidence: 98%
“…On the basis of sequence homology with Endo M, we cloned the ENG 1 cDNA from C. elegans, which is encoded by F01F1.10. 29) ENG 1 is a 433 amino acid polypeptide and exhibited 34% identity with Endo M. The human gene encoding ENGase was also reported around the same time. 30) ENGases from various animals including vertebrates and invertebrates belong to GH85 and the putative homologues are found from several plants, protozoa and fungi, but not from yeast Saccharomyces cerevisiae and Schizosaccharomyces pombe.…”
Section: )mentioning
confidence: 93%
“…The gene encoding Endo A was cloned later [81]. The primary structure of Endo A, composed of a 24 amino acid signal peptide and of a mature 621 amino acid protein, exhibited significant homology with a gene product from Caenorhabditis elegans, of unknown function at that moment, but later characterised [82], and no significant homology with any previously reported ENGases.…”
Section: Bacterial N-glycan-engasesmentioning
confidence: 99%
“…Caenorabditis elegans Endo CE [82] Homo sapiens Engase 1, ENGase [110] Plant N-glycan-ENGases Arabidopsis thaliana ENGase [183] Solanum lycopersicum Endo LE [121] Fungal N-glycan-ENGases…”
Section: Bacterial N-glycan-engasesmentioning
confidence: 99%